2001
DOI: 10.1209/epl/i2001-00165-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior of a single-crystal (110) Cr near the Néel temperature

Abstract: Using the 119Sn Mössbauer effect, the critical magnetic behavior of a single-crystal (110) Cr sample doped with ∼ 0.1 at% 119Sn was investigated in the vicinity of the Néel temperature, TN. The transition from a paramagnetic to an antiferromagnetic state was found to have a double character: it is continuous and has a hysteresis of ΔTN ≈ 1.3 K. The latter feature has been observed for the first time. The critical exponent β of the average hf field was found to be a continuous function of the reduced temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…We want to make the following remarks to this issue. Based on our previous studies of magnetism of chromium using the 119 Sn Mössbauer spectroscopy we found that (1) the third-order harmonics of the SDWs has amplitude and sign [9] in accord with the corresponding values revealed by the neutron (ND) diffraction study, (2) the value of the Néel temperature agrees within 1 K [10] with the value found from the ND study, (3) the value of the spin-flip temperature [11] agrees well with that determined with ND, and (4) the anomaly in CS(T) revealed in the present study occurs at the temperature that coincides with T N of a pure Cr alloy.…”
supporting
confidence: 67%
“…We want to make the following remarks to this issue. Based on our previous studies of magnetism of chromium using the 119 Sn Mössbauer spectroscopy we found that (1) the third-order harmonics of the SDWs has amplitude and sign [9] in accord with the corresponding values revealed by the neutron (ND) diffraction study, (2) the value of the Néel temperature agrees within 1 K [10] with the value found from the ND study, (3) the value of the spin-flip temperature [11] agrees well with that determined with ND, and (4) the anomaly in CS(T) revealed in the present study occurs at the temperature that coincides with T N of a pure Cr alloy.…”
supporting
confidence: 67%
“…One idea to align the Fe and Gd moments is to insert the correct number of monolayers (ML) of Cr between Fe and Gd. Cr is an antiferromagnet with a Néel temperature T N of 313 K [5], below which it attains a state of static spin density waves (SDW) along the [001]-direction, which can have complex variations [6]. In bulk Cr the AF order leads to an incommensurate spin density wave (ISDW) with a periodic modulation of the Cr magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…5. Noteworthy, the spectrum labelled with 60 is similar to the real spectrum measured at 295 K on a single-crystal sample of chromium [8] while the one labelled with 100 resembles the spectrum measured at 4.2 K on the same sample [20].…”
Section: Fundamental Harmonic Hmentioning
confidence: 55%
“…The experiments carried out by Street and Window gave evidence for that [4][5][6]. Since then several experimental and theoretical papers relevant to the issue were published [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Concerning the former, the following ones are worth mentioning: (1) observation of the spin-flip transition in Cr [7], (2) determination of the third-order harmonics of the SDWs in Cr [8], (3) determination of the effect of grain boundaries on the SDWs in Cr [14], (4) determination of the effect of vanadium on the SDWs in Cr [18], (5) study of the critical behavior of Cr around the Neel temperature [20], (6) observation of a huge spin-density enhancement in the pre surface zone of a single-crystal Cr [21][22][23]25].…”
Section: Introductionmentioning
confidence: 99%